Application of STATCOM to improve the LVRT of DFIG during RSC Fire-through Fault - Abdou, A.; Abu-Siada, Ahmed; Pota, H. (Institut Teknologi Sepuluh Nopember (ITS), 2012)
The use of doubly fed induction generators (DFIGs) in large wind energy conversion systems (WECS) has significantly increased during the last few years. The DFIG is interfaced to the AC network through a grid side voltage source converter (GSC) and a rotor side voltage source converter (RSC) to enable the variable speed operation of the wind turbine. Moreover, it provides reactive power support to the AC grid during disturbances. The sensitivity of DFIGs to external faults has motivated researchers to investigate the impact of various grid disturbances, such as voltage sag and short circuit faults, on the low voltage ride through (LVRT) capability of DFIGs. However, no attempts have been made to investigate the impact of converter internal faults on the LVRT of the DFIG-based WECS. In this paper, the impact of a fire-through fault when it occurs in the RSC on the DC-capacitor voltage, rotor current, and the LVRT capability of the DFIG is investigated. A STATCOM controller to mitigate the effects of this fault is proposed. The DFIG compliance with various recently released LVRT grid codes under the fire-through fault with and without the STATCOM is examined and compared. Simulation results indicate that fire-through fault has a severe impact on the DFIG voltage profile and the proposed controller is capable of bringing the voltage profile at the point of common coupling (PCC) to the nominal steady state level.